Benefit‐Risk Summary of Crizotinib for the Treatment of Patients With ROS1 Alteration‐Positive, Metastatic Non‐Small Cell Lung Cancer. (21st June 2016) - Kazandjian, Dickran; Blumenthal, Gideon M.; Luo, Lola; He, Kun; Fran, Ingrid; Lemery, Steven; Pazdur, Richard
Abstract : On March 11, 2016, after an expedited 5‐month review, the U.S. Food and Drug Administration expanded the crizotinib metastatic non‐small cell lung cancer (mNSCLC) indication to include the treatment of patients whose tumors harbor a ROS1 rearrangement. The approval was based on a clinically meaningful, durable objective response rate (ORR) in a multicenter, single‐arm clinical trial (ROS1 cohort of Trial PROFILE 1001) in patients with ROS1‐positive mNSCLC. The trial enrolled 50 patients (age range: 25–77 years) whose tumors were prospectively determined to have a ROS1 gene rearrangement by break‐apart fluorescence in situ hybridization (96%) or reverse transcriptase polymerase chain reaction (4%) clinical trial assays. Crizotinib demonstrated an ORR of 66% (95% confidence interval [CI]: 51%–79%) with a median duration of response of 18.3 months by independent radiology review and 72% (95% CI: 58%–84%) by investigator review. Patients received crizotinib 250 mg twice daily and had a median duration of exposure of 34.4 months. The toxicity profile in ROS1‐positive patients was generally consistent with the randomized safety data in the U.S. Product Insert from two ALK‐positive mNSCLC trials. The most common (≥25%) adverse reactions and laboratory test abnormalities included vision disorders, elevation of alanine transaminase and aspartate transaminase levels, nausea, hypophosphatemia, diarrhea, edema, vomiting, constipation, neutropenia, and fatigue. There were no treatment‐related deaths. A favorable benefit‐to‐risk evaluation led to the traditional approval of crizotinib for this new supplemental indication. Abstract : The FDA has expanded the crizotinib metastatic non‐small cell lung cancer indication to include treatment of patients whose tumors harbor a ROS1 rearrangement. The approval was based on a clinically meaningful, durable objective response rate (66%) in a multicenter, single‐arm clinical trial. Patients received crizotinib 250 mg twice daily; the median duration of exposure and of response was 34.4 and 18.3 months, respectively.